Can Counter‐Intuitive Halogen Bonding Be Coulombic?. Issue 12 (25th May 2021) - Murray, Jane S.; Politzer, Peter
Abstract: We use the term "counter‐intuitive" to describe an intermolecular interaction in which the electrostatic potentials of the interacting regions of the ground‐state molecules have the same sign, both positive or both negative. In the present work, we consider counter‐intuitive halogen bonding with nitrogen bases, in which both the halogen σ‐hole and the nitrogen lone pair have negative potentials on their molecular surfaces. We show that these interactions can be treated as Coulombic despite the apparent repulsion between the ground‐state molecules, provided that both electrostatics and polarization are explicitly taken into account. We demonstrate first that the energies of 20 counter‐intuitive interactions with four nitrogen bases can be expressed very well in terms of just two molecular properties: the electrostatic potential of the halogen σ‐hole and the average polarizability of the nitrogen base. Then we show that the same two properties can also represent the energies of an expanded data base that includes the 20 counter‐intuitive plus an additional 20 weak and moderately‐strong intuitive halogen bonding interactions (in which the σ‐hole potentials are now positive). Abstract : Coulombic or not ? The validity of the Coulombic interpretation has been challenged, as counter‐intuitive interactions appear impossible from the standpoint of electrostatics of the ground‐state molecules. Herein, we address the issue of counter‐intuitive interactions and whether (or not) they fit into the Coulombic framework.